INFLUÊNCIA DA ESTIMULAÇÃO ELÉTRICA E DA VELOCIDADE DE RESFRIAMENTO NA COR E NA MACIEZ DA CARNE BOVINA - MENEZES, Roberta (2008)
The technology of animal origin products increase considerably, and the meat with its commercial importance is the main focus in the technologic development, searching for less costs production, major regiment and mainly better quality of the final product, however, some aspects are not totally clear, among them it finds the electrical stimulation effect and the freezing temperature influencing in the meat quality. The aim of this research was to evaluate the electrical stimulation effect and the freezing speed, about aspects that influences the meat quality. Twenty Nellore bovines non gelding bred were slaughter, around 24 months, kept in feedlot. After bleeding, half animals of each group were electrically stimulated. The carcass were submitted to one of the freezing treatment, conventional and slowly. During the freezing it were registered the curves of temperature reduction and the carcass pH reduction. After the opening of the cameras, the animals were taken to the room where the bones were taken out and then strip loin (longissimus dorsi muscle) of 2.5 cm of thickness approximately, and strip loin steaks with 1.0 cm close to. After 30 minutes it were evaluated the steak color using the portable colorímetro in the structure CIE L*, a* and b*. The steaks were vacuum packed and kept in the stock camera in 0oC for 24 hours. After this period it was analyzed for cooking loss, shear force and length sarcomere. There was (p<0.05) effect of the cooling and the electrical stimulation method in the sarcomere length measure. The sample slowly freezing without electrical stimulation showed biggest lengths sarcomere than the ones freezing by the conventional method, however, in the conventional freezing with the electrical stimulation, the samples stimulated had biggest length sarcomere than the samples of carcass no electrically stimulated. There was effect (p<0.05) of the freezing method in the shear force. The sample freezing slowly had smaller force of shear force considering the same way of freezing. There was not effect (p>0.05) of the freezing method and the electrical stimulation use in the loss cooking and in the values of luminosity L*, a*, b* in the strip loin samples.